EFFECTIVENESS OF Daphnia sp ENRICHMENT WITH DIFFERENT LEVELS OF Spirulina platensis FLOUR ON COLOR BRIGHTNESS AND GROWTH OF KOI CARP (Cyprinus rubrofuscus) - Buhang, Dela Puspita; Juliana, Juliana; Mulis, Mulis (Asian Journal of Aquatic Sciences, 2024)
Koi (Cyprinus rubrofuscus) is one of the freshwater fish farming commodities that has an attractive color. Cultivators are trying to improve the quality of the color of this fish by adding a source of pigment. One is Spirulina, a source of natural pigments added to feed. Spirulina platensis has a content of B-carotene (28%) and Zeaxanthin (17%). This study aims to enrich Daphnia sp by using S.platensis flour to increase koi fish's color brightness and growth. This research was carried out for ±40 days at the Tatelu Freshwater Aquaculture Fisheries Center (BPBAT) Tatelu. The research method is experimental by applying a Complete Random Design (CRD) consisting of four treatments and three replicates. Treatment A (Control), B (3 g/L), C (5 g/L), D (7 g/L) S.platensis flour. The test fish used were 96 koi carp seeds with a length of 57 mm and a body weight of 5.47 g. The containers used are 12 aquariums measuring 30×40×40 cm3 with a volume of 48 L and fish stocking density of 8 fish. The data analysis used was Analysis of Variance, and a further test of the Smallest Real Difference (BNT) was carried out using the SPSS version 26.0 application. The results showed that the application of Daphnia sp enriched with S.platensis flour could have a real effect on the color brightness and specific growth rate of koi carp (p<0.05). The best treatment in this study was the administration of S.platensis flour as much as 7 g/L.